PS-048 Improving medicines reconciliation in pre-operative assessment of surgical patients. (24th February 2014) - Leung, C; Brunswicker, A; Yogarajah, A; Sparrow, S; Webdale, M; Irving, S; Lipp, A
Abstract : Background: In our large teaching hospital, Pre-Operative Assessments (POA) for general surgery patients are completed in a single visit by a multidisciplinary team comprising trained nurses, anaesthetist and junior doctors. Medicines reconciliation and completion of thromboprophylaxis risk assessment (TRA) are completed by junior doctors. For orthopaedic patients, these are completed by trained pharmacists. Missed doses as a result of incomplete POA for general surgery patients were identified as a major risk at our institution. Purpose: We carried out a prospective study comparing the reliability of medicines reconciliation performed by junior doctors compared to pharmacists, before and after implementation of three interventions that are listed below. Materials and methods: We collected data on completion rate of prescription charts and TRAs of all patients who attended POA for general surgery and orthopaedic for 2 weeks, and the number of missed doses for 2 weeks. Following that, the completion rate of all patients attending POA for general surgery was continuously monitored over a period of 22 weeks. A fishbone diagram was used to analyse the POA process and to identify possible targets for interventions. We implemented three interventions: All junior doctors receive a mandatory medicines reconciliation and TRA teaching session. Junior doctors to complete all prescription charts as a batch at the end of POA clinic. Patients were not permitted to be transferred to theatre without a complete prescription chart. Data were plotted in a run-chart for analysis. The attendance rate and reasons for nonattendance of junior doctors at POA were also recorded. Results: The completion rate of prescription charts and TRA for general surgery and orthopaedic patients was 43% and 94% respectively. Over a period of one week, 18 cases of missed doses were recorded. Following the first two interventions, the completion rate of prescription charts for general surgery patients increased to 45% and to 51% after the third intervention. Junior doctors attended only 44% of POA clinics, with the majority being kept away by other clinical commitments. Conclusions: Preventing medicines errors in elective surgical patients begins with accurate medicines reconciliation and completion of prescription charts at POA clinic. Our data revealed that junior doctors were not as reliable as trained pharmacists in completing prescription charts. Despite three interventions, the completion rate of prescription charts by junior doctors could not be raised to meet the standard of trained pharmacists. We therefore support the introduction of trained pharmacists to the POA clinics to manage medicines reconciliation and reduce medicines-related incidents. No conflict of interest.